Development and Conservation of Gonadal Primordial Germ Cells for Preservation of Local Chicken in Indonesia - Tatan Kostaman; S Sopiyana (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
One of the ex situ conservation techniques for poultry that recently developed was to collect primordial germ cell (PGC) or gonadal primordial germ cell (gPGC) that isolated from embryo development. Primordial germ cells (PGC) are embryonic cells that migrate to the gonads and form the precursors of gametes. The unique nature and accessibility of PGC during the early development provides an opportunity to manipulate the poultry germplasm, for example by forming germline chimeras. There are some stages that must be done through isolation and collection of PGC from its resources i.e. blastoderm, embryonic circulation blood and gonad. PGC collection originating from the gonads is one of existing PGC resources and technologies. gonadal PGC have advantages compared with other sources, namely (1) A large number of gonadal PGC can be taken from an embryo; and (2) A collection of gonadal PGC can be used in developing management systems of local avian germplasm conservation. This review is intended to describe the usefulness of isolation and collection technology of gonadal PGC as the local poultry germplasm conservation in Indonesia.